Studies in classical hebrew - Bar-Asher, Mosheh, 1939- (Studia Judaica (Walter de Gruyter & Co.) ;, 2013)
This volume collects studies of the classical Hebrew language by one of the foremost scholars of this language in our time. Moshe Bar-Asher has published dozens of studies of Hebrew, Aramaic, and Arabic, spanning nearly three thousand years of texts and dialects. Very few of his penetrating studies have been available in any European language, however. This volume presents 24 of them in English, dealing with the language of the Bible, the Dead Sea Scrolls, and Rabbinic Literature.